Risk Analysis Report as the Key Source for Ensuring Continuity of Production Processes - Jarosław Napiórkowski; Jerzy Stanik (Communications of International Proceedings, 2020)
The paper is oriented to methodological aspects of reporting the results of risk analysis in order to ensure the continuity of production processes. Its essence is to present the most important, current, and useful research issues and activities for the above. The reporting of outcomes from the risk analysis is understood as integrated notification on all limitations, uncertainties, assumptions, instability of legal regulations, and various areas of risk factors and their impact on the assessment of the security level of the production process. Performed literature studies allow the authors to notice a research gap in the form of a lack of effective research on improving current reporting systems, searching for and identifying sources of cyber threats, identifying threats and vulnerabilities, selecting the method of risk estimation, evaluation, and valuation in relation to ensuring the continuity of production processes. The paper describes the theoretical background and the methodology of developing a risk analysis report for the purpose of ensuring the continuity of production processes as a result of literature studies and own research. The scope of the article covers the following issues: the concept of the production process and its risk, business continuity management (BCMP) with traditional and author's approach. The key outcome presented within the paper is the proposition of an integrated risk analysis report as a key element in ensuring the continuity of the production process.
Keywords: Risk; analysis and risk assessment; risk reporting; Business Impact Analysis (BIA).